The Cognitive Approach to Syntax: The Role of Mental Representation in Language Structure - Pakpahan, Marnangkok (Journal of Humanities Research Sustainability, 2025)
Background. Language processing and syntactic structure are closely linked to the cognitive system and mental representation. Mental representation serves as an internal model that allows speakers to predict, interpret, and produce grammatically structured sentences. In recent years, research in psycholinguistics and cognitive neuroscience has increasingly highlighted the neural and cognitive mechanisms underlying syntactic processing. Understanding how mental representation interacts with syntax can help explain individual differences in language ability and processing efficiency. Purpose. This study aims to examine the role of mental representation in the construction and processing of syntactic structures. Specifically, the research investigates how cognitive factors such as working memory and attention influence the mental encoding and retrieval of syntactic patterns. Furthermore, the study seeks to understand the neural basis of syntactic processing and how different brain regions contribute to syntactic comprehension and production. Method. The research employs a qualitative approach combined with neuropsychological analysis. Data collection includes cognitive tests assessing working memory and attentional capacity, as well as brain imaging techniques such as functional MRI (fMRI) to observe neural activity during syntactic processing tasks. This multi-method approach provides both behavioral and neurological insights into the interplay between mental representation and syntax. Results. The findings show that brain regions such as the prefrontal cortex and Broca’s area exhibit significant activity during syntactic processing tasks. The level of brain activation correlates with individual differences in working memory and attention, indicating that cognitive capacity influences syntactic processing efficiency. Conclusion. Mental representation plays a critical role in syntactic structure formation and language processing. Cognitive factors, particularly working memory and attention, significantly contribute to the efficiency and accuracy of syntactic processing, highlighting the importance of integrating cognitive and neuropsychological perspectives in language research.